Estudio de la dinámica de vorticidad en el flujo estable alrededor de un cuerpo Ahmed (2016)
Numerical methods and simulations in engineering have become powerful tools for the design and analysis of systems, due to the generation of comparable results to those of experimentation. In particular, CFD simulations produce results that can be only interpreted by means of plots and visual representations of the main variables. These variables are in general the velocity and the pressure. Nevertheless, the understanding of data in terms of these variables can be restricted since some flow dynamics can be obscured. This is how enters the scene another important variable in fluid dynamics, the vorticity. In this manner, the aim of this document is to present a study of the flow around an Ahmed body in terms of the vorticity field, with the final purpose of discovering features and behaviors of the flow that are not so evident in the v-p fields. To achieve this, the results of a RANS simulation...